A systematic review of the costs and cost-effectiveness of clinical pharmacists on hospital ward rounds. (3rd September 2019) - Bullock, Brooke; Coombes, Ian; Mitchell, Charles; Donovan, Peter; Whitty, Jennifer A.
ABSTRACT: Introduction : There is a lack of good quality economic evidence for the inclusion of pharmacists on hospital ward rounds in addition to, or as an alternative to, traditional ward-based clinical pharmacy services. There has been no systematic review of the cost or cost-effectiveness of pharmacists attending and contributing on ward rounds. Areas covered : A literature search was conducted in Medline, Embase, Cochrane, and CINAHL and reported in accordance with the PRISMA guidelines in May 2019. As well, a search using Google Scholar and a targeted hand search were undertaken. Studies that reported any estimate of the cost or cost-effectiveness were included if pharmacist participation on inpatient hospital ward rounds was the predominant focus of the intervention. The identified studies were subsequently screened by three reviewers who extracted data on their clinical and economic design. A bias assessment was completed using the ROBINS-I tool. Expert opinion : Seven studies were identified investigating a clinical pharmacist's inclusion on hospital ward rounds where there was a cost estimated. However, none were deemed to be a full economic evaluation and all were found to be open to a serious risk of bias. Future evaluations should include a comparator group and investigate the cost and cost savings of the service, alongside their clinical outcomes.